A Multidimensional Concept of Mental Workload: A Systematic Review - Hidayat, Veny; Sumin, Sumin; Kartowagiran, Badrun; Ayriza, Yulia (Journal of Educational, Health and Community Psychology, 2022)
The concept of mental workload is fully used and leads to various theoretical and methodological models. For this purpose, we are conducted in the same way as a systematic review for understanding the concept and a factor that identifies work and work situations that affect personal tasks, or mental workload field. A systematic review was obtained from scientific papers issued from 2010-to 2021. Mental workload is multidimensional, so that a conceptual definition of mental workload should therefore integrally encompass the most elementary dimensions of mental workload. In general, most factors affected mental workloads, including working environments, individual differences, temporal pressure, and task difficulty/compliance complexity. Techniques for assessing subjective workloads are popular in several studies because of their ease of use and sensitivity to workload fluctuations. The NASATLX scale is the most common subjective technique and is used in a wide range of fields. Subjective and objective measurements cannot even measure all kinds of factors that affect mental distress. The main difficulty facing researchers is establishing standardized measurements of mental workload and its normal range so that effective comparisons can be made between groups of subjects. These results can provide measurement development recommendations using three approaches: subjective, objective, and behavioral.Keywords: mental workload; measurement; workload factors